Two sides of the same coin - how the application of effectuation and causation shapes business model elements throughout the development stages of digital start-ups. (15th August 2019) - Anagnou, Maria; Handrich, Matthias; Schnellbächer, Benedikt; Heidenreich, Sven
Nowadays, many digital start-ups fail in the early stages of their venture creation process. The main reason for the failure can often be found within the business model. Successful entrepreneurs agree on the fact that the destiny of a start-up highly depends on the decision-making ability of the respective entrepreneur. However, there is dissent in practice and academia whether decisions concerning the business model need to be made differently depending on the venture development stage. Some thought leaders recommend that entrepreneurs plan for every contingency in their business model (causation theory), while others favour a behaviour where the entrepreneur should work with the resources and the set of skills, which are currently available (effectuation theory). Using semi-structured expert interviews, our study provides first empirical evidence that effectuation and causation are no substituting but rather synergetic entrepreneurial approaches within business model development that are often applied simultaneously.